Comprehensive Anti-Bullying and Sexual Violence Education Program - Muhammad Abdul Aziz; Ratna Safitri; Ravi Satria; Putri Aprilia Choirismar; Raden Ilhammuddin Reiberor (Unram Journal of Community Service, 2025)
This activity on anti-bullying and sexual violence was held at SMA N 1 CEPOGO with the aim of increasing students' understanding and awareness of risky behaviors that can occur in the school environment. Using a quantitative approach, this activity was conducted through direct material delivery by the resource person, supported by presentation media, and a question-and-answer session as a means of clarification and student interaction. This socialization, attended by 33 tenth-grade students, took place in several stages: opening, material presentation, discussion, and closing. Based on the implementation results, it was found that many students did not clearly understand the forms of bullying and sexual violence beforehand. However, after socialization, they showed an increase in knowledge and awareness regarding the impact, prevention, and importance of reporting adverse events. This socialization program is effective in fostering student understanding and creating a safer, more comfortable, and supportive school environment for the learning process.